Gβγ-SNAP25 exocytotic brake removal enhances insulin action, promotes adipocyte browning, and protects against diet-induced obesity - Ryan P. Ceddia; Zack Zurawski; Analisa Thompson Gray; Feyisayo Adegboye; Ainsley McDonald-Boyer; Fubiao Shi; Dianxin Liu; Jose Maldonado; Jiesi Feng; Yulong Li; Simon Alford; Julio E. Ayala; et al. (The Journal of Clinical Investigation, 2023)
Negative regulation of exocytosis from secretory cells is accomplished through inhibitory signals from Gi/o GPCRs by Gβγ subunit inhibition of 2 mechanisms: decreased calcium entry and direct interaction of Gβγ with soluble N-ethylmaleimide–sensitive factor attachment protein (SNAP) receptor (SNARE) plasma membrane fusion machinery. Previously, we disabled the second mechanism with a SNAP25 truncation (SNAP25Δ3) that decreased Gβγ affinity for the SNARE complex, leaving exocytotic fusion and modulation of calcium entry intact and removing GPCR-Gβγ inhibition of SNARE-mediated exocytosis. Here, we report substantial metabolic benefit in mice carrying this mutation. Snap25Δ3/Δ3 mice exhibited enhanced insulin sensitivity and beiging of white fat. Metabolic protection was amplified in Snap25Δ3/Δ3 mice challenged with a high-fat diet. Glucose homeostasis, whole-body insulin action, and insulin-mediated glucose uptake into white adipose tissue were improved along with resistance to diet-induced obesity. Metabolic protection in Snap25Δ3/Δ3 mice occurred without compromising the physiological response to fasting or cold. All metabolic phenotypes were reversed at thermoneutrality, suggesting that basal autonomic activity was required. Direct electrode stimulation of sympathetic neuron exocytosis from Snap25Δ3/Δ3 inguinal adipose depots resulted in enhanced and prolonged norepinephrine release. Thus, the Gβγ-SNARE interaction represents a cellular mechanism that deserves further exploration as an additional avenue for combating metabolic disease.